Penerapan Tehnik Effleurage Massage Terhadap Penurunan Skala Nyeri Pada Ibu Post Partum Di Ruang Ponek RSUD Dr. Moewardi Surakarta - Merlina Yuliarti; Irma Mustika Sari; Alfida Fitri (Lembaga Pengembangan Kinerja Dosen, 2023)
Background; Effleurage massage is a form of massage using the palms of the hands that apply gentle pressure to the surface of the body in a circular direction repeatedly. The number of mothers giving birth in the Ponek room (Maternity Room) with January 01, 2021 - July 31, 2023 amounted to 1047 patients and 15 patients gave birth normally. Objective; To determine the results of implementation in the application of Effleurage Massage techniques to reduce the pain scale in postpartum mothers in the Ponek Room of Dr. Moewardi Surakarta Hospital. Method; This type of research is descriptive in the form of a case study. The approach taken uses a nursing care approach, planning, implementation and evaluation. The application instrument uses the Numeric Rating Scale (NRS) and checklist sheet as a measuring tool to determine the level of pain scale. Results; The results of the application using Effleurage Massage techniques found that respondents had a pain scale of 4 (moderate pain) down to 0 (none pain). Conclusion; There is a difference in pain scale before and after Effleurage Massage at Dr. Moewardi Surakarta Hospital.